Capital and Trade Flows in Europe and the Impact of Enlargement - Daniel Piazolo; Claudia M. Buch (Kiel Institute of World Economics (IfW), 2000)
The Eastern enlargement of the European Union (EU) is likely to give a further boost to trade and capital flows, yet empirical evidence on the possible magnitudes is still scarce. This paper uses four different datasets to estimate the determinants of international asset holdings and trade flows. We find in most regressions that EU membership has a significant effect. Based on additional simulations of the expected flows to ten transition economies, we conclude that for the EU candidates actual values are still far below expected ones in most cases. Consequently, we anticipate rising capital and trade flows with the approach of EU accession, in particular for the seven EU candidates besides the Czech Republic, Hungary and Poland.
Keywords: F15; F17; F36; F21; 330; EU Enlargement; International Asset Holdings; Trade; Gravity Model; Simulations; Internationale Kapitalmobilität; Internationale Wirtschaftsbeziehungen; EU-Erweiterung; Simulation; Gravitationsmodell; Schätzung; Kredit; international; Portfolio-Investition; Direktinvestition; EU-Staaten; Osteuropa